Forty studies that changed psychology explorations into the history of psychological research - Hock, Roger R. 1948- (Harlow, Essex, England Pearson Education Limited, 2015)
Summary "This unique book closes the gap between psychology textbooks and the research that made them possible by offering a first hand glimpse into 40 of the most famous studies in the history of the field, and subsequent studies that expanded upon each study's influence. Readers are able to grasp the process and excitement of scientific discovery as they experience an insider's look at the studies that continue today to be cited most frequently, stirred up the most controversy when they were first published, sparked the most subsequent related research, opened new fields of psychological exploration, and changed most dramatically our knowledge of human behavior." --Publisher's description.
I. Biology and human behavior -- 1. One brain or two?: The split brain in man / M. S. Gazzaniga -- 2. More experience = bigger brain: Brain changes in response to experience / M. R. Rosenzweig, E. L. Bennett, & M. C. Diamond -- 3. Are you a "natural?": Sources of human psychological differences: the Minnesota study of twins reared apart / T. Bouchard, [et al.] -- 4. Watch out for the visual cliff! / E. J. Gibson & R. D. Walk -- II. Perception and consciousness -- 5. Take a long look: The origin of form perception / R. L. Fantz -- 6. To sleep, no doubt to dream...: Regularly occurring periods of eye mobility and concomitant phenomena during sleep / E. Aserinsky & N. Kleitman -- 7. Unromancing the dream: The brain as a dream-state generator: an activation-synthesis hypothesis of the dream process / J. A. Hobson & R. W. McCarley -- 8. Acting as if you are hypnotized: Hypnotic behavior: a cognitive, social, psychological perspective / N. P. Spanos -- III. Learning and conditioning -- 9. It's not just about salivating dogs!: Conditioned reflexes / I. P. Pavlov -- 10. Little emotional Albert: Conditioned emotional responses / J. B. Watson & R. Rayner -- 11. Knock wood!: Superstition in the pigeon / B. F. Skinner -- 12. See aggression...do aggression!: Transmission of aggression through imitation of aggressive models / A. Bandura, D. Ross & S. A. Ross -- IV. Intelligence, cognition, and memory -- 13. What you expect is what you get: Teachers' expectancies: determinates of pupils' IQ gains / R. Rosenthal & L. Jacobson -- 14. Just how are you intelligent?: Frames of mind: the theory of multiple intelligences / H. Gardner -- 15. Maps in your mind? Cognitive maps in rats and men / E. c. Tolman -- 16. Thanks for the memories!: Leading questions and the eyewitness report / E. F. Loftus -- V. Human development -- 17. Discovering love: The nature of love / H. F. Harlow -- 18. Out of sight, but not out of mind: The development of object concept / J. Piaget -- 19. How moral are you?: The development of children's orientations toward a moral order: sequence in the development of moral thought / L. Kohlberg -- 20. In control and glad of it!: The effects of choice and enhanced personal responsibility for the aged: a field experiment in an institutional setting / E. J. Langer & J. Rodin -- VI. Emotion and motivation -- 21. A sexual motivation...: Human sexual response / W. H. Masters & V. E. Johnson -- 22. I can see it all over your face!: Constants across cultures in the face and emotion / P. Ekman & W. V. Friesen -- 23. Life, change, and stress: The social readjustment rating scale / T. H. Holmes & R. H. Rahe -- 24. Thoughts out of tune: Cognitive consequences of force compliance / L. Festinger & J. M. Carlsmith -- VII. Personality -- 25. Are you the master of your fate?: Generalized expectancies for internal versus external control of reinforcement / J. B. Rotter -- 26. Masculine or feminine...or both?: The measurement of psychological androgyny / S. L. Bem -- 27. Racing against your heart: Association of specific overt behavior pattern with blood and cardiovascular findings / M. Friedman & R. H. Rosenman -- 28. The one, the many: Individualism and collectivism: cross-cultural perspectives on self-ingroup relationships / H. Triandis, [et. al.] -- VIII. Psychopathology -- 29. Who's crazy here, anyway?: On being sane in insane places / D. L. Rosenhan -- 30. You're getting defensive again: The ego and the mechanisms of defense / A. Freud -- 31. Learning to be depressed: Failure to escape traumatic shock / M. E. P. Seligman & S. f. Maier -- 32. Crowding into the behavioral sink: Population density and social pathology / J. B. Calhoun -- IX. Psychotherapy -- 33. Choosing your psychotherapist: Meta-analysis of psychotherapy outcome studies / M. L. Smith & G. V. Glass -- 34. Relaxing your fears away: The systematic desensitization treatment of neuroses / J. Wolpe -- 35. Projections of who you are: Psychodiagnostics: a diagnostic test based on perception / H. Rorschach -- 36. Picture this!: Explorations in personality / H. A. Murray -- X. Social psychology -- 37. A prison by any other name...: The pathology of imprisonment / P. G. Zimbardo -- 38. The power of conformity: Opinions and social pressure / S. E. Asch -- 39. To help or not to help: Bystander intervention in emergencies: diffusion of responsibility / J. M. Darley & B. Latané -- 40. Obey at any cost?: Behavioral study of obedience / S. Milgram.
Authorized adaptation from the United States edition, published by Pearson Education, ©2013.
Global edition.
Includes bibliographical references and indexes.
Keywords: Psychology -- Experiments -- History -- 20th century -- Textbooks; Psychology, Experimental -- History -- 20th century -- Textbooks; Human experimentation in psychology -- History -- 20th century -- Textbooks